How can you be a Christian and an economist? The meaning of the Accra Declaration for today - Du Plessis, SA (Nederduitse Gereformeerde Teologiese Tydskrif, 2010)
The Accra Declaration offers a narrow ideological interpretation of the modern economy and proceeds to reject neoliberalism as the ideological foundation thereof. This article, in its comment on the economy, argues for a less ideological approach to public theology, using a two-step argument. Firstly, neoliberalism is neither a coherent ideology nor a plausible historical narrative. Economists, who are the presumed architects of neoliberalism, do not recognise the propositions attributed to them by either the Accra Declaration or the critical literature on neoliberalism. Secondly, the Accra Declaration’s ideological framework causes it to misrepresent both the nature of modern economies and their objective results. An alternative, less ideological approach would allow the Church to appreciate both the strengths and the many problems of market economies, and would allow it to work with economists in resolving these instead of rejecting the insights of modern economics.